Structural health monitoring systems of long span bridges in Turkey and lessons learned from applications - Apaydin, Nurdan Memişoglu; Zülfikar, Abdullah Can; Cetindemir, Oguzhan (International Society for Structural Health Monitoring of Intelligent Infrastructure, ISHMII, 2021)
Long-span bridges constitute one of the most important lifelines in the countries where they are constructed since they shorten the route of transportation by providing passage through large waterways such as rivers, channels, dams and sea. Due to its geographical location, Turkey is a transit country between Asia and Europe. As the long-span bridges are subject to heavy traffic and seismic hazard in Turkey, great importance is attached to the monitoring of their structural health and also performing their maintenance in a timely and cost-effective manner. These bridges pose maintenance challenges due to their sizes. Because of their high towers and hard-to-access cables in general, the most reliable method of monitoring the structural condition of such bridges under service is to build structural health monitoring (SHM) systems. In this study, SHM systems of long-span bridges in Turkey, which are among the largest bridges across the world, were described. Characteristics of these systems utilized in the bridges were explained in detail. In addition, the SHM data acquired on the Second Bosphorus Bridge (the Fatih Sultan Mehmet Bridge) during a recent offshore event, the Silivri Earthquake (Mw 5.8), 26th September of 2019, were analyzed. The findings were validated with experimental research presented in the literature and the comparison indicated a good agreement to identify the bridges' dynamic characteristics. Finally, the problems encountered in SHM systems due to the characteristics of the bridges were explained and recommendations were provided for future applications. © 2022 Elsevier B.V., All rights reserved.
10th International Conference on Structural Health Monitoring of Intelligent Infrastructure, SHMII 2021 -- Porto -- 179266
Keywords: extreme loads; long-span bridges; monitoring objectives; SHM system